Pigmented Neuroepithelial Tumgur Of Infancy - P. S. Chari; A. K. Banerjee (Indian Journal of Plastic Surgery)
A case of pigmented neuroepithelial tumour of infancy involving the maxilla is presented. Recent knowledge of its multiceatric origin and capacity to metamorphose into a neuroblastoma necessitate a reappraisal in the policy of its management. A correct histopathological diagnosis is essential for proper surgery which is curative in large majority of cases. Rarity of the lesion leading to lack of awarencess and mistaken diagnosis of malignent lesion may in turn in ths create problems management and prognosticetion.